2019
DOI: 10.1016/j.compstruct.2018.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the damping properties of unidirectional composites by incorporating carbon fibers with a thin viscoelastic coating

Abstract: This is a repository copy of Optimizing the damping properties of unidirectional composites by incorporating carbon fibers with a thin viscoelastic coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As long as the same model is employed to calculate both fiber and composite moduli, the predicted composite moduli may be expected to be reasonably accurate. However, given that the composite cylinders model has been convincingly validated in our recent works on viscoelastic properties of unidirectional composites [11,31], there seems to be no obvious reason for us for not adopting this validate classical micromechanical model in our present study.…”
Section: Comparing Micromechanical Predictions With the Experimental Measurementsmentioning
confidence: 77%
See 1 more Smart Citation
“…As long as the same model is employed to calculate both fiber and composite moduli, the predicted composite moduli may be expected to be reasonably accurate. However, given that the composite cylinders model has been convincingly validated in our recent works on viscoelastic properties of unidirectional composites [11,31], there seems to be no obvious reason for us for not adopting this validate classical micromechanical model in our present study.…”
Section: Comparing Micromechanical Predictions With the Experimental Measurementsmentioning
confidence: 77%
“…It has recently been shown by Gusev and Kern [11] using a frequency domain finite element method, that direct numerical estimates of complex effective viscoelastic moduli of common carbon and glass fibre reinforced unidirectional composites are in excellent agreement with such classical analytical results. This recent work is a part of a broad research program [11][12][13][14][31][32][33][34] that has demonstrated that the GSCS predictions are generally remarkably accurate and technologically very helpful for design of both elastic, viscoelastic and thermoelastic properties of fiber and particulate composites with both uncoated and coated inclusions.…”
Section: Determination Of the Viscoelastic Constants Of The Unidirectional Compositementioning
confidence: 99%
“…The use of dynamic mechanical analyzers (DMA) has become dominant [39,40]. Recent works reported damping factors of CFRPs determined using DMA-type methods [41][42][43][44][45]. Note that shear damping factors were not considered in these low-frequency damping studies since torsional vibration generators are not readily available and their need was weak.…”
Section: Resultsmentioning
confidence: 99%
“…Kern et al. presented frequency-domain finite element estimates for unidirectional fiber composites with viscoelastic coating [8]. More works have proved that the damping property of CFRP can be improved effectively by coating the carbon fabric with viscoelastic material [9,10].…”
Section: Introductionmentioning
confidence: 99%